Solution to the Reich–Walczak conformity problem according to Belynsky–Lavrentyev - Ryazanov, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
A positive answer is given to the Reich–Walczak problem relative to conformality in the Belinskii–Lavrent'ev sense of quasiconformal mappings at a point in the case of an arbitrary modulus of the complex characteristic and under an appropriate selection of its argument.